Power in Modern Javanese Short Stories - Yosep B. Margono-Slamet (FKIP, Universitas Palangka Raya, 2025)
This article analzses sixteen short stories in modern Javanese literature. Those short stories were published between 2003 and 2005 in Panjebar Semangat, a Javanese weekly periodical in Surabaya. Using Anderson’s concept of power in Java as the main theoretical framework, I delve into the sixteen short stories to understand how power operates after the 1998 Indonesia’s Reformation. In addition, I also use Anderson’s, Geertz’s, and Magnis-Suseno’s concepts of harmony in Javanese society as the second theoretical framework to analyze how the sixteen short stories reflect the relationship between the rulers and the people. The analysis shows that the sixteen short stories are loaded with the corrupt power causing disharmony in modern Javanese and Indonesian societies. The corrupt power in Indonesia did not only happen during the New Order regime but also in the Reformation Order regime. After the Reformation, people hoped that those in power would become much better in creating welfare, prosperity and justice for the people, but they were as corrupt as or even more corrupt than those during the New Order regime. The corruption of power has many manifestations which cause further distance between the rulers and the people, and thus creating disharmony in Javanese society. Since most authors of Javanese literature are from the ordinary people, they take side with the common people. Even though the analyzed short stories are far from being the voices of all people in Java, at least they represent the voice of the voiceless.